Aplikasi untuk Monitoring Jaringan IoT Menggunakan Algoritma Address Shuffling dengan HMAC - Elvan Alandi; Agustinus Noertjahyana; Justinus Andjarwirawan (Jurnal Infra, 2020)
With the increasing market of the Internet of Things and Wireless Sensor Network (WSN). Increasing network security on the Internet of Things is important. Internet of Things is used starting from smart homes, smart campuses, smart cities, etc. so securing the Internet of Things network is more important than securing ordinary local networks. In addition, IoT devices have weaknesses in computing capabilities and storing sensitive data. There are four main types of weaknesses in the network, namely address spoofing attacks, false address conflicts, address exhaustion attacks and negative reply attacks.The method used is Address shuffling with HMAC. This method is run by the DHCPv6 server (Dynamic Host Configuration Protocol) as a network coordinator and is monitored by the Android application to secure the Internet of Things network. DHCPv6 server is used on the Internet of Things network because it is faster and easier to control through the server, can be used on large networks and stop and restart commands can be done on the server. Additionally, when a DHCPv6 server has a problem, this will not interrupt other devices on one network.The result of this program is a monitoring application that is able to notify users of attacks and the network is able to minimize four weaknesses in the network. So that later this application can help users to take preventive actions against attacks on the network.